2018
DOI: 10.1002/pbc.27216
|View full text |Cite
|
Sign up to set email alerts
|

Randomized web‐based physical activity intervention in adolescent survivors of childhood cancer

Abstract: An interactive, rewards-based intervention designed to increase MVPA is feasible in adolescent survivors of childhood cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(127 citation statements)
references
References 28 publications
2
115
1
9
Order By: Relevance
“…Supervised interventions containing a physical activityeducational and/or exercise intervention in a group setting improved physical activity, quality of life, cardiovascular, physical and metabolic outcomes of cardiovascular diseases [57,58]. Interventions focusing on physical activity or healthy diet of young cancer survivors are practical, feasible and generally well accepted by the participants [54,55,90].…”
Section: Discussionmentioning
confidence: 99%
“…Supervised interventions containing a physical activityeducational and/or exercise intervention in a group setting improved physical activity, quality of life, cardiovascular, physical and metabolic outcomes of cardiovascular diseases [57,58]. Interventions focusing on physical activity or healthy diet of young cancer survivors are practical, feasible and generally well accepted by the participants [54,55,90].…”
Section: Discussionmentioning
confidence: 99%
“…88,89 Alternatively, several small RCTs have evaluated home-based mobile health interventions, but reported no significant differences in physical activity levels after 10-24 weeks, suggesting that structured exercise and/or supervised exercise may be required to improve cardiovascular endpoints. 90,91 An RCT evaluating the efficacy of a 12-month home-based aerobic and resistance exercise on cardiovascular risk factors among 150 childhood cancer survivors is ongoing. 92…”
Section: Exercise Interventionsmentioning
confidence: 99%
“…29 Studies incorporating a FitBit or other electronic activity monitor found trackers to be acceptable to AYAs. 26,27,30 Taken together, these studies suggest that an in-person supervised intervention may have good initial impact but could be enhanced by incorporating mobile interventions that are acceptable to AYA and more likely to be integrated into daily life. No studies to date have combined the in-person group-based approach enhanced with mobile technology to capitalize on the strengths of each approach.…”
Section: Introductionmentioning
confidence: 87%
“…[23][24][25] Few studies specifically target AYA survivors of pediatric cancers. [26][27][28][29][30][31] Of those studies targeting AYA survivors of pediatric cancer, almost all found positive but not statistically significant improvements in physical activity and fitness outcomes, which may be attributed to small sample size. Of note, a group-based community intervention found significant improvements in physical activity and fitness outcomes postintervention, but gains were not maintained at follow up.…”
Section: Introductionmentioning
confidence: 99%